Entitlement: The big problem in medical education we will not talk about. (3rd May 2020) - Liao, Lester
Abstract: Entitlement is a problem in medical education that has received relatively little attention. First, it is felt by educators, who often feel pressured to conform curricula and evaluations to satisfy learner demands and administrative pressures lest their careers are penalized. Second, entitlement affects the medical system, as entitled physicians are less empathetic and focus more on personal goods rather than patient needs. This shifts the humanistic basis for medicine. Thirdly, entitlement is problematic for learners, as constant accommodations ironically undermine self-reliance and adaptability. Constantly meeting these demands can diminish gratitude and overall happiness. To address this issue, learners must acknowledge the problem and seek remedies to it themselves, as top-down interventions will likely be rebuffed. Rather than focusing solely on the learning environment, solutions should also empower learners to engage their environment in effective and productive ways. This should include correcting cognitive distortions that lead learners to expect administrative interventions in all circumstances perceived as harmful. Other solutions include practicing gratitude and developing work friendships. While certainly not all learners are entitled and some environmental amendments should be made, learners and educators must realize that entitlement is shaping medical culture and collectively take steps to mitigate its negative effects.